My World - Wilkinson, Jonny (London Headline Book Publishing, 2004)
Jonny Wilkinson opens up to reveal what it is like to be the world's most famous rugby player and an international sporting superstar. This work gives an insight into his motivations, thoughts, hopes and fears as he discusses topics as far ranging as playing for England, his all-time heroes, and becoming a celebrity.
Include Illustrations.
English Biography.
Keywords: Rugby Union football players -- England -- Wilkinson, Jonny